Keberlakuan Pasal 100 Kitab Undang-Undang Hukum Pidana Nomor 1 Tahun 2023 dalam Studi Kasus Pembunuhan Berencana Brigadir Norfriansyah Yosua Hutabarat - Gregorius Eka Januario Carvalho Amaral Borgeous; Fareh Prameswari; Adelia Trisna Juniar (Harmonization : Jurnal Ilmu Sosial, Ilmu Hukum, dan Ilmu Ekonomi, 2023)
The purpose of this article is to show that the principle of legality as stated in the Criminal Code (KUHP) Article 1 can be the basis for the potential application of the Criminal Code Article 100 to the case of premeditated murder by the defendant Ferdy Sambo. The method used in determining and analyzing the said potential is normative juridical using two approaches. First, Conceptual Approach, namely views on doctrines, concepts, and legal principles regarding legal development. Second, the Statute Approach, which is an approach by studying the rules and regulations of a case studied based on the law. Thus, the potential validity of the Criminal Code Article 100 is still wide open if the legal process carried out by Ferdy Sambo within three years has not been resolved.